New Challenges in the United States - O'Neil, Robert (International Higher Education, 2009)
Academic freedom in American higher education evolves in curious and often unpredictable ways. For those who teach at public or state-supported institutions, the courts play a major role in defining the scope of such freedom. For faculty at independent or private colleges and universities, whose policies are seldom subject to court review, standards are provided by organizations such as the American Association of University Professors. Some faculties at institutions of both types may also be protected by collective bargaining agreements. After a decade or so with relatively few critical tests of the rights and liberties of US scholars, the past year or two has brought academic freedom to the fore in dramatic fashion. Three current tests merit special attention: the cases of John Yoo, William Robinson, and Ward Churchill.